LEKTUR KLASIK KEPENDIDIKAN ISLAM GENRE ADAB - Robiatul Adawiyah; Syaripuddin Daulay (Jurnal Bilqolam Pendidikan Islam, 2021)
The existence of a study of some classical literature shows that there are many educational ideas, adab or academic ethics that have been studied by classical scholars so that they can be introduced and studied. The research method used in this article is to examine the existing literature related to the theme of the article. And as a result, Ibn Jama'ah details the keys to the success of an educator scholar. Regarding the concept of teacher/educator and its relation to teaching, Ibn Jama'ah detailed the Islamic etiquette that guides educators, including being consistent in drawing closer to Allah in every condition, maintaining knowledge as the Salaf scholars guarded knowledge, glorifying and glorifying it, strengthening self with the nature of zuhud towards the world, purifying his knowledge from actions making it a means of reaching the world, distancing his knowledge from the contempt of income, disgraceful character, and things that are makruh both in terms of good customs and syara'. Adab that must exist in students as the key to success includes: First, etiquette with oneself. Second, etiquette with teachers/educators/clerics. Third, etiquette with friends. Fourth, etiquette with the knowledge/lessons learned